PENGARUH KELOMPOK REFERENSI DAN PENDIDIKAN KEWIRAUASAHAAN TERHADAP MINAT ERWIRAUSAHA SISWA JURUSAN BISNIS DARING DAN PEMASARAN DI SMKN 1 JOMBANG - Jaka Adi Saputra; Patrikha, Finisica Dwijayati (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
This study aims to analyze the influence of reference groups and entrepreneurship education on the entrepreneurial interest of students in the Online Business and Marketing Department at SMKN 1 Jombang. The research employs a quantitative approach using multiple linear regression analysis. Data were collected through questionnaires involving 100 student respondents. The findings indicate that reference groups, including family, peers, teachers, and influencers, have an impact on students' entrepreneurial interest. Entrepreneurship education also shows a positive influence, particularly through relevant curricula, qualified educators, and supporting facilities. Reference groups and entrepreneurship education have both direct and simultaneous effects on the entrepreneurial interest of students in the Online Business and Marketing Department at SMKN 1 Jombang. These findings highlight the importance of synergy between entrepreneurship education and support from reference groups in encouraging students to become confident and innovative entrepreneurs.